(untitled) (Architecture Image Studies, 2026)
In Greater Nokoué (Benin) and Greater Lomé (Togo), there is a lack of access to formal and affordable housing. The objective of this paper is to examine the daily resilience strategies developed by tenants in Greater Nokoué and Greater Lomé to gain access to housing. It is based on a mixed methodological approach combining tenant surveys (159 in Greater Nokoué and 251 in Greater Lomé) and semi-structured interviews (28 in Greater Nokoué and 17 in Greater Lomé). The results reveal various coping mechanisms used to secure housing, maintain livelihoods, and foster a sense of belonging in environments marked by exclusion and informality. The field results also show that, in Greater Nokoué, strategies are based on occupying precarious housing characterized by poor hygiene and sanitation. In Greater Lomé, in addition to occupying makeshift housing, cohabitation is marked by tense relations and neighborhood conflicts. These findings show that, while these strategies allow for short-term adaptation, they often reproduce spatial inequalities and expose these populations to social and economic instability. Given this imperative, it is urgent to take into account these difficulties in accessing housing when promoting resilient and accessible cities for all, an important criterion in the definition of a sustainable city.